The 1st International Electronic Conference on Catalysis Sciences 2020
DOI: 10.3390/eccs2020-07758
|View full text |Cite
|
Sign up to set email alerts
|

Benzeneseleninic Acid in the Photo-Catalyzed Hydroxy-Selenylation of Styrenes

Abstract: We established a new visible-light-mediated protocol for the regioselective βhydroxyselenylation of olefins, employing benzeneseleninic acid as substrate. Regarding a novel approach, the benzeneseleninic acid emerges as an efficient and affordable reagent to be used as an electrophilic selenium source that can be easily converted to selenium-based radical species under visible-light conditions. In this sense, the photocatalytically formed PhSe• radical can react directly with unsaturated substrates, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In contrast to the electrophilic activation strategy, the mechanistically distinct selenofunctionalization of alkenes has been explored by generating the selenium radical species under electrochemical and photochemical conditions (Scheme b). In addition, different photocatalysts have been successfully utilized for the oxyselenylation, aminoselenylation, and selenoarylation of alkenes under visible light conditions, where the photochemically generated PhSe· radicals were oxidized to the PhSe+ cation by molecular oxygen. While the generation of PhSe+ cationic species via the photochemical activation of diselenides under air might be a valid mechanistic interpretation in electron-rich alkenes, a recent study by Liu and Ling demonstrated an alternative reaction pathway for the visible-light-induced oxidative coupling of alkenes and diselenides, involving the PhSe· radical addition to alkenes followed by trapping the carbon-based radicals with molecular oxygen to give α-aryl selenomethyl ketones .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the electrophilic activation strategy, the mechanistically distinct selenofunctionalization of alkenes has been explored by generating the selenium radical species under electrochemical and photochemical conditions (Scheme b). In addition, different photocatalysts have been successfully utilized for the oxyselenylation, aminoselenylation, and selenoarylation of alkenes under visible light conditions, where the photochemically generated PhSe· radicals were oxidized to the PhSe+ cation by molecular oxygen. While the generation of PhSe+ cationic species via the photochemical activation of diselenides under air might be a valid mechanistic interpretation in electron-rich alkenes, a recent study by Liu and Ling demonstrated an alternative reaction pathway for the visible-light-induced oxidative coupling of alkenes and diselenides, involving the PhSe· radical addition to alkenes followed by trapping the carbon-based radicals with molecular oxygen to give α-aryl selenomethyl ketones .…”
mentioning
confidence: 99%
“…In addition, different photocatalysts have been successfully utilized for the oxyselenylation, aminoselenylation, and selenoarylation of alkenes under visible light conditions, where the photochemically generated PhSe· radicals were oxidized to the PhSe+ cation by molecular oxygen. While the generation of PhSe+ cationic species via the photochemical activation of diselenides under air might be a valid mechanistic interpretation in electron-rich alkenes, a recent study by Liu and Ling demonstrated an alternative reaction pathway for the visible-light-induced oxidative coupling of alkenes and diselenides, involving the PhSe· radical addition to alkenes followed by trapping the carbon-based radicals with molecular oxygen to give α-aryl selenomethyl ketones . Inspired by the photochemical generation of selenium radical species under visible light conditions, a radical selenofunctionalization of alkenes was envisioned as a unified way of introducing multiple functional groups under aerobic conditions (Scheme c).…”
mentioning
confidence: 99%